2016
DOI: 10.1002/acn3.288
|View full text |Cite
|
Sign up to set email alerts
|

A randomized placebo‐controlled lovastatin trial for neurobehavioral function in neurofibromatosis I

Abstract: ObjectiveLovastatin has been shown to reverse learning deficits in a mouse model of Neurofibromatosis Type 1 (NF1), a common monogenic disorder caused by a mutation in the Ras‐MAPK pathway and associated with learning disabilities. We conducted a randomized double‐blind placebo‐controlled trial to assess lovastatin's effects on cognition and behavior in patients with NF1.MethodForty‐four NF1 patients (mean age 25.7+/−11.6 years; 64% female) were randomly assigned to 14 weeks of lovastatin (N = 23; maximum dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 39 publications
0
50
0
1
Order By: Relevance
“…Subsequent translational trials in human NF1 have shown mixed results. Improvements in verbal and non‐verbal memory were reported within a 12‐week phase 1 observational study of lovastatin in 23 children aged 10–17 years (Acosta et al., ) and in a 14‐week RCT of lovastatin in 44 10–50 years olds (Bearden et al., ); an n = 7 case series from the former cohort showed evidence of treatment normalising pseudoresting state functional connectivity in areas of the default mode network (Chabernaud et al., ). Four days of high‐dose (200 mg) lovastatin improved synaptic plasticity and phasic alertness, as measured with trans‐cranial magnetic stimulation, in a case‐controlled study of 11 adults with NF1 (Mainberger et al., ).…”
Section: Moving To the Level Of Neural Mechanismmentioning
confidence: 99%
“…Subsequent translational trials in human NF1 have shown mixed results. Improvements in verbal and non‐verbal memory were reported within a 12‐week phase 1 observational study of lovastatin in 23 children aged 10–17 years (Acosta et al., ) and in a 14‐week RCT of lovastatin in 44 10–50 years olds (Bearden et al., ); an n = 7 case series from the former cohort showed evidence of treatment normalising pseudoresting state functional connectivity in areas of the default mode network (Chabernaud et al., ). Four days of high‐dose (200 mg) lovastatin improved synaptic plasticity and phasic alertness, as measured with trans‐cranial magnetic stimulation, in a case‐controlled study of 11 adults with NF1 (Mainberger et al., ).…”
Section: Moving To the Level Of Neural Mechanismmentioning
confidence: 99%
“…8 More recently, results from a small randomized controlled trial in children and adults with NF1 reported beneficial effects of lovastatin on learning and memory. 9 In the current study, we tested the hypothesis that 16 weeks of lovastatin will result in cognitive, behavioral, and quality-of-life improvements for children with NF1. The safety profile of lovastatin was also evaluated.…”
mentioning
confidence: 99%
“…4 In contrast to our findings, results from a recent study of adults (n 5 30; 80 mg/d) and children (n 5 14; 40 mg/d) with NF1 for 14 weeks suggested possible beneficial effects of lovastatin on working memory, verbal memory, and adult self-reported internalizing problems. 9 Unfortunately, a high dropout rate (27%) resulted in only 32 evaluable patients (15 placebo, 17 lovastatin), reducing statistical power. Failure to analyze the ITT population and to adjust for baseline performance may also have resulted in overestimation of the effect size and led to nonrandom attrition of participants.…”
mentioning
confidence: 99%
“…Moreover, in clinical trials, FDA-approved statins, which showed beneficial effects in mouse models, were tested on neurobehavioral phenotypes in NF1 patients (Bearden, Hellemann, Rosser, Montojo, Jonas, Enrique et al, 2016;Krab, de GoedeBolder, Aarsen, Pluijm, Bouman, van der Geest et al, 2008a;Mainberger, Jung, Zenker, Wahllander, Freudenberg, Langer et al, 2013;van der Vaart, Plasschaert, Rietman, Renard, Oostenbrink, Vogels et al, 2013). Although small trials with lovastatin suggested beneficial effects of statins on cognitive function in NF1 patients (Bearden et al, 2016;Mainberger et al, 2013), large scale randomized placebo-controlled trials with simvastatin were not successful in showing efficacy against cognitive impairments (Krab et al, 2008a;van der Vaart et al, 2013), which suggests the necessity of developing next generation treatment strategies. As reviewed here, the RAS-MAPK pathway is controlled in specific ways by a distinctive set of regulators, depending on cell type.…”
Section: Discussionmentioning
confidence: 99%